Creating eco-friendly behaviors: Environmental education and plastic waste management - Christianty Christianty; Mohammad Ali (Inovasi Kurikulum, 2025)
This study explores the critical role of environmental education in addressing plastic waste management, focusing on integrating programs like Indonesia’s Adiwiyata initiative and outdoor education. Through a literature review of peer-reviewed articles, books, and reports, this research highlights how environmental education fosters pro-environmental behaviors, particularly in reducing plastic pollution. The study emphasizes the importance of practical, hands-on learning experiences to instill a sense of environmental responsibility among students. Despite the potential of programs like Adiwiyata, challenges such as administrative prioritization over genuine behavioral change remain. Outdoor education is presented as a key strategy for bridging the gap between theory and practice, empowering students to become “green ambassadors” within their communities. The findings suggest that improving waste management systems and environmental education are essential for mitigating plastic pollution. Combining education, policy, and public awareness, this holistic approach is necessary for a sustainable future where plastic waste no longer poses a significant threat to ecosystems or human health.   Abstrak Penelitian ini meneliti peran krusial pendidikan lingkungan dalam pengelolaan sampah plastik, dengan menyoroti integrasi program seperti inisiatif Adiwiyata di Indonesia serta pendidikan berbasis luar ruangan. Melalui tinjauan literatur dari artikel ilmiah, buku, dan laporan, penelitian ini menyoroti bagaimana pendidikan lingkungan dapat mendorong perilaku pro-lingkungan, terutama dalam mengurangi polusi plastik. Studi ini menekankan pentingnya pengalaman belajar praktis untuk menanamkan tanggung jawab lingkungan pada peserta didik. Meskipun program seperti Adiwiyata memiliki potensi, tantangan seperti prioritas administratif dibandingkan perubahan perilaku yang nyata masih ada. Pendidikan luar ruangan diidentifikasi sebagai strategi utama untuk menjembatani kesenjangan antara teori dan praktik, serta memberdayakan peserta didik menjadi "duta hijau" di komunitas mereka. Hasil penelitian menunjukkan bahwa peningkatan sistem pengelolaan limbah, bersama dengan pendidikan lingkungan, sangat penting untuk mengurangi polusi plastik. Pendekatan holistik ini, yang menggabungkan pendidikan, kebijakan, dan kesadaran publik, diperlukan untuk masa depan yang berkelanjutan di mana limbah plastik tidak lagi menjadi ancaman signifikan bagi ekosistem atau kesehatan manusia. Kata Kunci: adiwiyata; manajemen sampah plastik; pendidikan lingkungan; pendidikan luar ruang